The Effectiveness of the Planetarium Android Learning Application Virtual Observatory on Solar System Material - Imronah, Imronah; Parmin, Parmin; Widiatningrum, Talitha (Journal of Innovative Science Education, 2022)
The COVID-19 pandemic has affected education worldwide, and online learning is a solution to keep learning activities going. Learning in Indonesia also applies online learning by utilizing smartphones and the internet. The current education curriculum uses Education Technology (edutech), so innovation is needed in developing learning media, one of which is an Android learning application in the form of a Virtual Planetarium Observatory. The research objectives are (1) to analyze the validity of the Virtual Planetarium Observatory, (2) to analyze the feasibility of the Virtual Planetarium Observatory (3) to analyze the effectiveness of the Virtual Planetarium Observatory. This research is a research and development (R&D) research design pretest-posttest control group design with the research subjects of class VII students of MTs Al Hadi Girikusuma Mranggen Demak. The validation results of media experts and media validity experts are very valid, with 93%. The feasibility of the teacher's response and the student's response to the media is very feasible, with a percentage of 86%. The media's effectiveness is pretty effective in increasing student learning outcomes with a rate of 72%. Based on the N-Gain test, the experimental class was 0.72 in the high category, while the control class was in the middle category at 0.58. The significance of the effectiveness based on the t-test with a value of Sig 0.028 < 0.05 means a significant difference between before and after using the Virtual Planetarium Observatory on improving student learning outcomes. Based on the study results, it can be concluded that the Virtual Planetarium Observatory can improve student learning outcomes on solar system material.